Satisfaction of Postgraduate Residents with Mini-CEX: A Student-Centered Evaluation at Rawalpindi Medical University - Khalid, Tabinda; Ahmed, Malik Irfan; Naqvi, Rubaba Abid; Riaz, Samra; Haq, Aqsa Ikram Ul; Rasheed, Masooda (Journal of Rawalpindi Medical College, 2026)
Objective: To evaluate postgraduate residents’ satisfaction with Mini-CEX as a formative assessment tool, and to use their feedback to guide improvements in its implementation at Rawalpindi Medical University. Methods- A structured and validated questionnaire comprising 18 closed-ended items was distributed using a five-point Likert scale. It assessed trainees’ understanding of Mini-CEX, perceptions of its educational value, facilitator involvement, and its impact on personal, professional, and clinical development. It also collected trainee-driven feedback to inform future improvements in Mini-CEX sessions. Results- Among 135 eligible trainees, 116 completed the questionnaire, resulting in a response rate of 85.9%. Most trainees expressed satisfaction with Mini-CEX, noting improvements in clinical skills, personal development, and professional growth. The mean satisfaction score across all domains was 3.6. However, several respondents reported gaps in orientation, unclear format, and inconsistent feedback and facilitator engagement. Conclusion- These findings highlight the need for clearer orientation regarding Mini-CEX objectives and practical strategies to improve time management during assessments. To address concerns about facilitator engagement, establishing a formal feedback channel between trainees and instructors could improve the quality of interactions. Strengthening communication and aligning expectations will enhance the educational value of Mini-CEX in postgraduate training. Keywords: Clinical Competence, Education, Medical, Graduate, Educational Measurement, Professional Satisfaction, Workplace